Forward and inverse dynamics modeling of human shoulder-arm musculoskeletal system with scapulothoracic constraint. Issue 11 (17th August 2020) - Hu, Tingli; Kühn, Johannes; Haddadin, Sami
Abstract: In this work, we extend the modeling techniques of human shoulder-arm musculoskeletal dynamics by 1) proposing an extended model with 12 joint degrees of freedom and 27 muscles (modeled as 42 musculotendinous actuators) that is capable of most physiologically and anatomically possible movements, 2) proposing a forward dynamics model driven by muscle activation, where the scapulothoracic constraint is formulated as an anatomically consistent force field, and 3) applying the state-of-the-art inverse dynamics solution on this model. We experimentally validate it against electromyograms for 10 activities of daily living. This validated shoulder-arm musculoskeletal model may e.g., serve as a reference plant model in studying human motor control or as part of a human simulator in the future.